Effects of Therapeutic Hypothermia and Minimal Enteral Nutrition on Short-Term Outcomes in Neonates with Hypoxic–Ischemic Encephalopathy: A 10-Year Experience from Oman - Manoj Malviya; Sathiya Murthi; Dhanya Jayaraj; Vidya Ramdas; Fadia Nazir Malik; Valsala Nair; Nusrabegam Marikkar; Mukesh Talreja; Tariq Sial; Prakash Manikoth; Renjan Varghese; Khalsa Ali Al Ramadhani; et al. (Children)
Background: Therapeutic hypothermia (TH) is the standard treatment for moderate to severe hypoxic–ischemic encephalopathy (HIE) in developed countries, but data on its safety and efficacy in low-middle-income countries are limited and often conflicting. The impact of enteral feeding during TH remains inadequately explored. We aimed to examine TH’s effects on mortality and brain injury and evaluate the safety and effectiveness of minimal enteral feeding during TH. Here, we report our single-center experience with TH over a 10-year period”. Methods: A total of 187 neonates with moderate to severe HIE who underwent cooling were included in this retrospective study. Post-rewarming MRI scans were scored using a validated MRI scoring system. The primary outcomes were mortality and composite outcomes of mortality and brain injury. Results: The mortality rate was 3% in moderate and 25% in severe cases (p < 0.001). Overall, 85% (160/187) of neonates received minimal enteral nutrition. Multivariate regression analysis revealed that the severity of HIE at admission (OR 3.4 (1.03–11.6); p < 0.04) and gestational age (OR: 0.624 (0.442–0.882); p < 0.008) were independent predictors of composite outcomes of death and brain injuries. MRI score was a strong predictor of mortality (AUC: 0.89; p < 0.001) and of ability to orally feed at discharge (AUC: 0.73; p < 0.001). Conclusions: Mortality rates associated with TH in infants with moderate–severe HIE align with those in high-income countries, and minimal enteral feeding during TH is safe. The severity of HIE, MRI scores, and feeding status are important predictors of outcomes.